Factors influencing missed nursing care in public hospitals in Australia: An exploratory mixed methods study. (26th August 2019) - Albsoul, Rania; FitzGerald, Gerard; Finucane, Julie; Borkoles, Erika
Summary: Background: Missed nursing care (MNC) is a significant health care issue that impacts on the quality of health care and patient safety. It refers to delayed or omitted aspects of nursing care (totally or partially). MNC is an under‐researched area in the Australian health care context. Objective: This research sought to further explore the MNC phenomenon in the context of an acute care hospital and to identify its common elements and the factors influencing its occurrence. Design: A convergent parallel mixed methods design was employed involving secondary analysis of routinely collected hospital data and a survey of 44 nursing staff using the MISSCARE survey instrument. The two sources of data were converged to address the objective. Findings: The study found that the most common elements of missed nursing care include failure of patient ambulation, emotional support for patients and/or family, and the provision of full documentation. These elements are consistent with previous international studies conducted in acute care hospital settings. This study identified that local context impacting on MNC was also important and included interruptions to workflow, "perceived" lack of management support, poor handover, and communication breakdown between the nursing team and medical staff. Conclusion: Consideration of the local health care context is foundational in understanding the MNC phenomenon. The findings of this research may help nursing managers mitigate the possible effects of MNC and therefore improve patient safety in their acute care environment. Additional multisite studies are required to further explore factors associated with MNC in both general and local contexts.